Incidencia del manejo del retorno en la producción del cultivo de banano subgrupo cavendish en la provincia de El Oro - Nivelo Nagua, Jefferson Manuel (2017)
Ecuador is currently ranked first among banana producers worldwide. It is worth noting the participation of the province of El Oro as one of the provinces with the highest production of bananas, thanks to the fertility of its lands and to the Optimum environments that allow to obtain a product of quality. Bananas are considered one of the largest industries that generates income and sources of work, contributes significantly to GDP, generating positive results in the exports that are made to the different countries, which undoubtedly prefer the Ecuadorian banana because of its exceptional agronomic characteristics Which differentiate it from the rest. At present, banana (Musa x paradisiaca L.) is considered as the first source of income as far as agricultural production in the Ecuadorian state is concerned, which generates positive results in the daily exports to the different countries of the world , Which undoubtedly prefer the Ecuadorian banana because of its exceptional agronomic characteristics, which differentiate it from the rest. It should be noted that Ecuador, despite being the first exporter of quality bananas in the world, does not reach the levels of productivity that other producing countries present, due to the poor technical management in selection of the return, affecting early mother-child-grandson relationship , Causing delays in the children of succession, reducing in this way the profitability of the crop. Through the integrated management of selection, nutrition and early stimulation of the grandchild, using the "condom" technique, by cutting lengths between mother-child and grandchild, to establish the increase of return in each of the farms sample. The present research is fully focused on determining how to decrease the time of harvest between mother-child-grandson, and thus increase productivity per unit of production, through the correct selection of return and its early stimulation with the technique of "condom" , Which was applied and performed in three areas of the province of GOLD, located in the cantons of El Guabo T1, Machala T2 and Passage T3, in each of the treatments it was proposed to consider 20 plants per treatment and 20 control plants. The variables evaluated were son height, grandchild height, number of hands, number of fingers, hand weight, rachis weight, total cluster weight, ratio. The data were analyzed in the SPSS version 23 program. One-way ANOVA and the Tukey 0.05 probability test. The results indicate that there are significant differences in each parameter analyzed, the greatest development of the return was in the T1 located in the Guabo canton, the T2 located in Machala presented the lowest growth percentage and the lowest ratio. The T3 located in passage obtained an average of development and an acceptable ratio, the exposed results indicate that the selection of the return, early stimulation and the mother-son-grandson relationship management in each production unit can be controlled to improve the numbers Of cuts per plant per year, improving the profitability of banana plantations.